Development of Frequency Based Taste Receptors Using Bioinspired Glucose Nanobiosensor - TermehYousefi, A.; Tateno, K.; Bagheri, S.; Tanaka, H. (Nature Publishing Group, 2017)
A method to fabricate a bioinspired nanobiosensor using electronic-based artificial taste receptors for glucose diagnosis is presented. Fabricated bioinspired glucose nanobiosensor designated based on an artificial taste bud including an amperometric glucose biosensor and taste bud-inspired circuits. In fact, the design of the taste bud-inspired circuits was inspired by the signal-processing mechanism of taste nerves which involves two layers. The first, known as a type II cell, detects the glucose by glucose oxidase and transduces the current signal obtained for the pulse pattern is conducted to the second layer, called type III cell, to induce synchronisation of the neural spiking activity. The oscillation results of fabricated bioinspired glucose nanobiosensor confirmed an increase in the frequency of the output pulse as a function of the glucose concentration. At high glucose concentrations, the bioinspired glucose nanobiosensor showed a pulse train of alternating short and long interpulse intervals. A computational analysis performed to validate the hypothesis, which was successfully reproduced the alternating behaviour of bioinspired glucose our nanobiosensor by increasing the output frequency and alternation of pulse intervals according to the reduction in the resistivity of the biosensor.